Fluorine-containing polyurethane water lubrication composite material, preparation method and bearing

By using fluorine-containing polyurethane prepolymers and polytetrafluoroethylene in polyurethane water-lubricated bearing materials, the compatibility and dispersion of polytetrafluoroethylene are improved, and the compatibility and dispersion of polyurethane water-lubricated bearing materials are solved. The problem of insufficient performance has achieved better water and wear resistance.

CN119286240AInactive Publication Date: 2025-01-10JIHUA LAB

Patent Information

Application Number
CN202411805665.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polyurethane water-lubricated bearing materials have poor dispersion in high-polar polytetrafluoroethylene, resulting in poor interfacial bonding, affecting performance, and insufficient water resistance, making it easy to engage in motion system under heavy load and low speed.

Method used

Using fluoro-containing polyurethane prepolymers and polytetrafluoroethylene, reinforced fibers and other raw materials, the compatibility and dispersion of polytetrafluoroethylene are improved through specific reaction and curing processes, and the fluoro-containing polyurethane water-lubricated composite materials are prepared to improve the Water and wear resistance of the material.

Benefits of technology

The water absorption and friction coefficient of the material are significantly reduced, and the water resistance and wear resistance are improved, so that the fluoropolyurethane water-lubricated composite materials show excellent stability and low friction characteristics during the friction process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286240A_ABST
    Figure CN119286240A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer water lubrication materials, and provides a fluorine-containing polyurethane water lubrication composite material, a preparation method and a bearing, a dihydroxyl-terminated perfluoropolyether monomer and a polyurethane prepolymer are adopted to prepare a fluorine-containing polyurethane prepolymer, so that a fluorine-containing group is introduced into polyurethane, polytetrafluoroethylene micro powder is added, and the fluorine-containing polyurethane water lubrication composite material is prepared. The fluorine-containing polyurethane water lubrication composite material which can be used for bearing manufacturing is prepared; according to the fluorine-containing polyurethane material provided by the invention, the dihydroxyl-terminated perfluoropolyether monomer is introduced into the polymer, so that the problem that agglomeration is easy to occur when polytetrafluoroethylene is added is solved, and the water resistance and the wear resistance are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of polymer water-lubricating materials, and specifically relates to a fluorine-containing polyurethane water-lubricating composite material and a preparation method and a bearing. Background Art

[0002] Water-lubricated bearings use water directly as the lubricating medium, which can effectively avoid water pollution caused by lubricating oil leakage and are environmentally friendly. Water-lubricated bearings not only save a lot of lubricating oil, but also simplify the traditional shaft structure design, eliminate the complex sealing structure design work, and make the later maintenance and care of the bearings more convenient. At the same time, water has a large specific heat, which can effectively take away the surface heat of the friction pair during the friction process, and has a significant cooling effect on friction heat.

[0003] At present, the commonly used polymer materials for water-lubricated bearings are mainly: rubber composites, ultra-high molecular weight polyethylene, polyetheretherketone, polyphenylene sulfide, polytetrafluoroethylene and polyurethane materials. Polyurethane (PU) is a block copolymer with strong structural and functional designability. Compared with other polymer bearing materials, PU is more suitable for sand-water conditions. The sand particles entering the friction interface are wrapped by the elastic deformation of the material, and are brought into the groove during the rotation of the shaft. Finally, they are washed away from the bearing by water, effectively avoiding excessive wear on the shaft. However, the limitations of PU as a base material for water-lubricated bearings have also been discovered, such as insufficient water resistance, and the possibility of motion system bite when sliding under heavy load and low speed. Summary of the invention

[0004] The purpose of this application is to solve the deficiencies of the prior art and provide a fluorinated polyurethane water-lubricated composite material and a preparation method and a bearing, specifically adopting the following technical solutions: A fluorine-containing polyurethane water-lubricated composite material, the raw materials of which include fluorine-containing polyurethane prepolymer and polytetrafluoroethylene; the fluorine-containing polyurethane prepolymer is prepared from terminal dihydroxy perfluoropolyether monomer and polyurethane prepolymer.

[0005] In the existing field of polyurethane water-lubricated bearing polymer materials, polytetrafluoroethylene is generally added to the polyurethane system to further improve the lubricity of the material. However, due to the small polarity and low surface energy of polytetrafluoroethylene, its dispersibility in the high-polarity polyurethane system and poor interface bonding are poor, so polytetrafluoroethylene often agglomerates, which seriously affects the performance of the polyurethane system. The fluorinated polyurethane water-lubricated composite material provided in the present application has improved compatibility with polytetrafluoroethylene, so that polytetrafluoroethylene can be evenly and tightly dispersed in the fluorinated polyurethane water-lubricated composite material.

[0006] In some preferred implementations, the terminal bishydroxyl perfluoropolyether monomer is at least one of 1H,1H,11H,11H-perfluoro-3,6,9-trioxoundecan-1,11-diol, polyperfluoroethoxymethoxydifluoroethyl PEG ether and perfluoropolyether diol.

[0007] In some preferred implementations, the mass ratio of the terminal bishydroxyl perfluoropolyether monomer to the polyurethane prepolymer is (0.01-0.1):1.

[0008] In some preferred implementations, the mass ratio of polytetrafluoroethylene to fluorine-containing polyurethane prepolymer is (0.02-0.1):1.

[0009] In some preferred implementations, the raw material further includes reinforcing fibers.

[0010] In some preferred implementations, the reinforcing fiber is at least one of carbon fiber, glass fiber and aramid fiber; the mass ratio of the reinforcing fiber to the fluorine-containing polyurethane prepolymer is (0.05-0.2):1; the average particle size of the reinforcing fiber is 400 mesh-2000 mesh; and the average particle size of the polytetrafluoroethylene is 1 μm-20 μm.

[0011] On the one hand, the present application also provides a method for preparing a fluorinated polyurethane water-lubricated composite material, comprising the following steps: S1, reacting a terminal dihydroxyl perfluoropolyether monomer with a polyurethane prepolymer to obtain a fluorine-containing polyurethane prepolymer; S2. Then, the fluorinated polyurethane prepolymer and the remaining raw materials are subjected to a curing reaction to obtain a fluorinated polyurethane water-lubricated composite material.

[0012] In some preferred implementations, the specific process of S1 is: drying the terminal dihydroxy perfluoropolyether monomer at 105°C for 24 hours, then mixing it with the polyurethane prepolymer, and reacting it under nitrogen protection and 80°C-95°C for 2 hours-4 hours to obtain a fluorine-containing polyurethane prepolymer; the specific process of S2 is: heating the fluorine-containing polyurethane prepolymer to 70°C-80°C, then mixing it with the remaining raw materials to obtain a first mixture, then mixing the melted curing agent with the first mixture, degassing, and then pouring it into a mold, hot pressing for 30 min-60 min, the hot pressing pressure is 5 MPa-10 MPa, and the temperature is 120°C; then demolding, and finally curing at 90°C for 15 h-24 h; to obtain a fluorine-containing polyurethane water-lubricated composite material.

[0013] In some preferred implementations, the curing agent used in the curing reaction is at least one of 4,4'-methylenebis(2-chloroaniline) and 4,4'-methylenebis(3-chloro-2,6-diethylaniline); the mass ratio of the curing agent used in the curing reaction to the fluorinated polyurethane prepolymer is (0.2-0.3):1.

[0014] On the other hand, the present application also provides a bearing comprising the above-mentioned fluorine-containing polyurethane water-lubricated composite material.

[0015] The beneficial effects of this application are: The present application adopts terminal dihydroxy perfluoropolyether monomer and polyurethane prepolymer to prepare fluorinated polyurethane prepolymer, which improves the compatibility with polytetrafluoroethylene, reduces water absorption and friction coefficient, and makes the provided fluorinated polyurethane water-lubricated composite material have excellent water resistance and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Shown is a schematic diagram of the preparation process mechanism of fluorinated polyurethane prepolymer; Figure 2 The graph shows the test results of the friction coefficient variation curves of the samples of Examples 1 to 4 and Comparative Examples 1 to 3 over time; Figure 3 Shown are the wear volume test results of samples of Examples 1 to 4 and Comparative Examples 1 to 3; Figure 4 Shown are the water absorption test results of samples of Examples 1 to 4 and Comparative Examples 1 to 3; Figure 5 Shown is a schematic diagram of contact angle testing of Example 1 and Comparative Examples 1-2; Figure 6 Shown is a graph showing the test results of the friction coefficient variation over time of samples in Examples 5 to 6. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of this application, so as to fully understand the purpose, scheme and effect of this application. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.

[0018] Example 1 A fluorine-containing polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: Preparation of fluorinated polyurethane prepolymer: First, dry the terminal dihydroxy perfluoropolyether monomer (1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol) in a vacuum drying oven for 24 hours at 105°. Then, 100 parts of polyurethane prepolymer (Yuanxing Material UC-70D) and 1 part of 1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol were mixed and added into a three-necked flask, nitrogen was passed through, mechanical stirring was performed, and the fluorinated polyurethane prepolymer was obtained by reacting at 90°C for 2 hours.

[0019] Preparation of fluorinated polyurethane water-lubricated composite material: First, 100g of the above-mentioned fluorinated polyurethane prepolymer was heated to 70°C, 5g of polytetrafluoroethylene powder and 10g of carbon fiber were added, and then 25.4g of 4,4'-methylenebis(2-chloroaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90°C for 16h to obtain a fluorinated polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0020] Example 2 A fluorine-containing polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: Preparation of fluorinated polyurethane prepolymer: First, dry the terminal dihydroxy perfluoropolyether monomer (1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol) in a vacuum drying oven for 24 hours at 105°. Then, 100 parts of polyurethane prepolymer (Yuanxing Material UC-70D) and 2 parts of 1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol were mixed and added into a three-necked flask, nitrogen was passed through, mechanical stirring was performed, and the fluorinated polyurethane prepolymer was obtained by reacting at 90°C for 3 hours.

[0021] Preparation of fluorinated polyurethane water-lubricated composite material: First, 100g of the above-mentioned fluorinated polyurethane prepolymer was heated to 70°C, 5g of polytetrafluoroethylene powder and 10g of carbon fiber were added, and then 24g of 4,4'-methylenebis(2-chloroaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90°C for 16h to obtain a fluorinated polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0022] Example 3 A fluorine-containing polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: Preparation of fluorinated polyurethane prepolymer: First, dry the terminal dihydroxy perfluoropolyether monomer (1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol) in a vacuum drying oven for 24 hours at 105°. Then, 100 parts of polyurethane prepolymer (Yuanxing Material UC-70D) and 3 parts of 1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol were mixed and added into a three-necked flask, nitrogen was passed through, mechanical stirring was performed, and the fluorinated polyurethane prepolymer was obtained by reacting at 90°C for 3 hours.

[0023] Preparation of fluorinated polyurethane water-lubricated composite material: First, 100g of the above-mentioned fluorinated polyurethane prepolymer was heated to 70°C, 5g of polytetrafluoroethylene powder and 10g of carbon fiber were added, and then 22.7g of 4,4'-methylenebis(2-chloroaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven for curing at 90°C for 16h to obtain a fluorinated polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0024] Example 4 A fluorine-containing polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: Preparation of fluorinated polyurethane prepolymer: First, dry the terminal dihydroxy perfluoropolyether monomer (1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol) in a vacuum drying oven for 24 hours at 105°. Then, 100 parts of polyurethane prepolymer (Yuanxing Material UC-70D) and 4 parts of 1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxonadecane-1, 11-diol were mixed and added into a three-necked flask, nitrogen was passed, mechanical stirring was performed, and the reaction was carried out at 90°C for 3 hours to obtain a fluorinated polyurethane prepolymer.

[0025] Preparation of fluorinated polyurethane water-lubricated composite material: First, 100g of the above-mentioned fluorinated polyurethane prepolymer was heated to 70°C, 5g of polytetrafluoroethylene powder and 10g of carbon fiber were added, and then 21.4g of 4,4'-methylenebis(2-chloroaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven for curing at 90°C for 16h to obtain a fluorinated polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0026] Example 5 A fluorine-containing polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: Preparation of fluorinated polyurethane prepolymer: First, the terminal dihydroxy perfluoropolyether monomer (polyperfluoroethoxymethoxydifluoroethyl PEG ether (Fluorolink® E10-H)) was dried in a vacuum drying oven for 24 hours at a temperature of 105°. Then, 100 parts of polyurethane prepolymer (Yuanxing Material UC-70D) and 6 parts of polyperfluoroethoxymethoxydifluoroethyl PEG ether (Fluorolink® E10-H) were mixed and added to a three-necked flask, nitrogen was passed through, mechanical stirring was performed, and the fluorinated polyurethane prepolymer was obtained by reacting at 90°C for 4 hours.

[0027] Preparation of fluorinated polyurethane water-lubricated composite material: First, 100g of the above-mentioned fluorinated polyurethane prepolymer was heated to 70°C, 4g of polytetrafluoroethylene powder and 6g of glass fiber were added, and then 23g of 4,4'-methylenebis(3-chloro-2,6-diethylaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90°C for 16h to obtain a fluorinated polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0028] Example 6 A fluorine-containing polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: Preparation of fluorinated polyurethane prepolymer: First, dry the terminal dihydroxyl perfluoropolyether monomer (perfluoropolyether diol) in a vacuum drying oven for 24 hours at a temperature of 105°. Then, mix 100 parts of polyurethane prepolymer (Yuanxing Material UC-70D) with 8 parts of perfluoropolyether diol and add them into a three-necked flask, pass nitrogen, stir mechanically, and react at 90°C for 4 hours to obtain a fluorinated polyurethane prepolymer.

[0029] Preparation of fluorinated polyurethane water-lubricated composite material: First, 100g of the above-mentioned fluorinated polyurethane prepolymer was heated to 70°C, 8g of polytetrafluoroethylene powder and 15g of aramid fiber were added, and then 21g of 4,4'-methylenebis(3-chloro-2,6-diethylaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90°C for 16h to obtain a fluorinated polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0030] Comparative Example 1 A pure polyurethane water lubricating material, the preparation method of which comprises the following steps: First, 100g of polyurethane prepolymer (Yuanxing Material UC-70D) was heated to 70℃, and 27g of 4,4'-methylenebis(2-chloroaniline) was heated to 110℃ to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120℃) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90℃ for 16h to obtain a pure polyurethane water-lubricated material; it was used as a bearing sample for performance testing.

[0031] Comparative Example 2 A polyurethane water lubricating material, the preparation method of which comprises the following steps First, 100g of the polyurethane prepolymer (Yuanxing Material UC-70D) in Example 1 was heated to 70°C, and 25.4g of 4,4'-methylenebis(2-chloroaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90°C for 16h to obtain a polyurethane water-lubricating material; it was used as a bearing sample for performance testing.

[0032] Comparative Example 3 A polyurethane water-lubricated composite material, the preparation method of which comprises the following steps: First, 100g of the polyurethane prepolymer (Yuanxing Material UC-70D) in Example 1 was heated to 70°C, 5g of polytetrafluoroethylene powder was added, and 25.4g of 4,4'-methylenebis(2-chloroaniline) was heated to 110°C to melt. Then the two were mixed, mechanically stirred for 30s, and immediately transferred to a vacuum degassing barrel for degassing for 60s, poured into a mold, and hot-pressed for 30min (pressure 5MPa, temperature 120°C) using a flat vulcanizer. Finally, the mold was removed and transferred to an oven, and cured at 90°C for 16h to obtain a polyurethane water-lubricated composite material; it was used as a bearing sample for performance testing.

[0033] Performance Testing and Result Discussion Friction coefficient performance test: The test was conducted using an Rtec reciprocating friction and wear tester with a load of 15 N, a frequency of 5 Hz, and a stroke of 6 mm. Bearing steel was selected as the friction pair and a 3% NaCl solution was used as the test environment. The friction coefficient performance of Examples 1 to 4 and Comparative Examples 1 to 3 was tested, and the experimental results were as follows: Figure 2 and Figure 6 shown.

[0034] Figure 2 The graphs show the test results of the friction coefficient variation curves of the samples of Examples 1 to 4 and Comparative Examples 1 to 3 over time. Among them, Comparative Example 1 is a pure polyurethane sample with the largest friction coefficient, reaching 0.28. In Comparative Example 2, due to the introduction of fluorine-containing groups, the advantages of low surface energy and low friction coefficient of fluorine compounds are given, and the friction coefficient is significantly reduced to about 0.2; in Comparative Example 3, due to the further introduction of polytetrafluoroethylene lubricating fillers, the friction coefficient is further reduced, and the initial friction coefficient can be reduced to about 0.1, but as time goes by, the surface is constantly worn, and finally the friction coefficient increases again. In Example 1, compared with Comparative Example 3, due to the introduction of reinforcing fibers, the mechanical properties of the sample can be further improved, and it is more wear-resistant. Therefore, the sample maintains a low friction coefficient during the entire test time. It can be seen that Examples 1 to 4 all have very low friction coefficients.

[0035] Figure 6 The friction coefficient of the samples of Example 5-6 is shown as a curve of the test results of the time variation. Among them, Example 5 and Example 6 show a relatively stable friction coefficient. Figure 2 The performance of Examples 5 and 6 is significantly improved compared with Comparative Examples 1-3. The friction coefficients of Examples 5 and 6 are stably lower than those of Comparative Examples 1-3 at all stages. Compared with Examples 1-4, the overall friction coefficient performance of Examples 5 and 6 is not much different from that of Examples 1-4.

[0036] Wear volume test: The volumes of Examples 1 to 4 and Comparative Examples 1 to 3 after the friction coefficient performance test were calculated using a white light interferometer. The results are as follows: Figure 3 shown.

[0037] It can be seen that compared with Comparative Example 1, due to the introduction of fluorine-containing groups, the friction force and the wear volume in Comparative Example 2 are reduced. The friction coefficient is further reduced by adding polytetrafluoroethylene lubricating filler. In Examples 1 to 4, due to the further introduction of reinforcing fibers, the friction coefficient is reduced and the wear resistance is also improved, so the wear volume is the lowest.

[0038] Water absorption performance test: The samples of Examples 1 to 4 and Comparative Examples 1 to 3 were separately sampled and immersed in salt water for 144 days to observe the changes in water absorption. The results are as follows: Figure 4 shown.

[0039] It can be seen that the water absorption rate of pure polyurethane is about 1.4%. After the introduction of fluorine-containing groups, the water absorption rate is significantly reduced to 0.63%. After adding polytetrafluoroethylene powder, since polytetrafluoroethylene is also hydrophobic, the water absorption rate is further reduced to 0.4%. It can be seen that the water absorption rates of the samples in Examples 1 to 4 are all less than 0.5%, which is much lower than that of pure polyurethane samples, and have more excellent water resistance.

[0040] Contact angle hydrophilicity performance test: Hydrophilicity refers to the affinity of a material surface for water, and the contact angle is an important parameter to measure the wetting properties of a liquid on a material surface. Specifically, if the static water contact angle of a material surface is less than 90°, the material surface is hydrophilic, that is, water wets the solid more easily, and the smaller the contact angle, the better the wettability.

[0041] Therefore, the contact angle tester can be used to test the hydrophilicity of the sample to illustrate the wettability of the material. Figure 5 As shown: Depend on Figure 5 It can be seen that Example 1 in the figure was compared with Comparative Examples 1 and 2, wherein the pure polyurethane sample of Comparative Example 1 has a higher hydrophilicity, with a contact angle of 71.1°; after the introduction of fluorine-containing functional groups in Comparative Example 2, the hydrophilicity decreased significantly, with a contact angle of 84.3°; after further introduction of polytetrafluoroethylene micropowder and carbon fiber in Example 1, the hydrophilicity further decreased, with a contact angle of 87.6°; this indicates that the fluorine-containing polyurethane water-lubricated composite material provided in the present application is prepared.

[0042] Although the description of the present application has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims by reference to the attached claims in view of the prior art, thereby effectively covering the intended scope of the present application. In addition, the above describes the present application with the embodiments foreseeable by the inventor, the purpose of which is to provide a useful description, and those non-substantial changes to the present application that have not yet been foreseen may still represent equivalent changes to the present application.

Claims

1. A fluorinated polyurethane water-lubricated composite material, characterized in that: The raw materials include fluorine-containing polyurethane prepolymer and polytetrafluoroethylene; the fluorine-containing polyurethane prepolymer is prepared from terminal dihydroxyl perfluoropolyether monomer and polyurethane prepolymer.

2. The fluorinated polyurethane water-lubricated composite material according to claim 1, characterized in that: The terminal dihydroxyl perfluoropolyether monomer is at least one of 1H, 1H, 11H, 11H-perfluoro-3, 6, 9-trioxoundecan-1, 11-diol, polyperfluoroethoxymethoxydifluoroethyl PEG ether and perfluoropolyether diol.

3. The fluorinated polyurethane water-lubricated composite material according to claim 1, characterized in that: The mass ratio of the terminal dihydroxy perfluoropolyether monomer to the polyurethane prepolymer is (0.01-0.1):

1.

4. The fluorinated polyurethane water-lubricated composite material according to claim 1, characterized in that: The mass ratio of the polytetrafluoroethylene to the fluorine-containing polyurethane prepolymer is (0.02-0.1):

1.

5. The fluorinated polyurethane water-lubricated composite material according to any one of claims 1 to 4, characterized in that: The raw material also includes reinforcing fibers.

6. The fluorinated polyurethane water-lubricated composite material according to claim 5, characterized in that: The reinforcing fiber is at least one of carbon fiber, glass fiber and aramid fiber; and / or, the mass ratio of the reinforcing fiber to the fluorine-containing polyurethane prepolymer is (0.05-0.2):1; and / or, the average particle size of the reinforcing fiber is 400 mesh-2000 mesh; and / or, the average particle size of the polytetrafluoroethylene is 1 μm-20 μm.

7. A method for preparing the fluorinated polyurethane water-lubricated composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, reacting the terminal dihydroxy perfluoropolyether monomer with the polyurethane prepolymer to obtain the fluorine-containing polyurethane prepolymer; S2. Then, the fluorine-containing polyurethane prepolymer and the remaining raw materials are subjected to a curing reaction to obtain the fluorine-containing polyurethane water-lubricated composite material.

8. The preparation method according to claim 7, characterized in that: The specific process of S1 is: drying the terminal dihydroxy perfluoropolyether monomer at 105°C for 24 hours, then mixing it with the polyurethane prepolymer, reacting it under nitrogen protection and 80°C-95°C for 2 hours-4 hours to obtain the fluorine-containing polyurethane prepolymer; and / or, the specific process of S2 is: heating the fluorine-containing polyurethane prepolymer to 70°C-80°C, then mixing it with the remaining raw materials to obtain a first mixture, then mixing the melted curing agent with the first mixture, degassing, then pouring it into a mold, and hot pressing it for 30 minutes-60 minutes. The pressure of the hot pressing is 5 MPa-10 MPa and the temperature is 120°C; then demolding, and finally curing at 90°C for 15 hours-24 hours; obtaining the fluorine-containing polyurethane water-lubricated composite material.

9. The preparation method according to claim 7, characterized in that: The curing agent used in the curing reaction is at least one of 4,4'-methylenebis(2-chloroaniline) and 4,4'-methylenebis(3-chloro-2,6-diethylaniline); and / or the mass ratio of the curing agent used in the curing reaction to the fluorinated polyurethane prepolymer is (0.2-0.3):

1.

10. A bearing, characterized in that: The invention comprises the fluorine-containing polyurethane water-lubricated composite material according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Sliding bearing material of elastoplastic polymer alloy

    CN102153852A

  • Wear resistant self-lubricating polyformaldehyde and preparation method thereof

    CN102675819A

  • Water lubricated bearing with high bearing capacity and self lubricity

    CN103788623A

  • Rolling sliding part

    US6121208A

Cited By

  • Composite nano-particle with core-chain cross-linked structure, preparation method of composite nano-particle and water-based lubricant

    CN121271616A